2020
DOI: 10.1007/s40894-020-00142-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organized Activities in Supporting Youth Moral and Civic Character Development: A Review of the Literature

Abstract: Organized activities have been championed as an important youth setting to nurture character development through childhood and adolescence, but scholars have yet to document the state of research on activities and youth character. Using guidelines from the Preferred Reporting Items for Systematic Reviews and Meta-analyses Statement (PRISMA, Moher et al., PLoS Med 6(7):e1000097, 2009), this study conducts an extensive review of previous research in order to provide a comprehensive understanding of the various w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…As mentioned earlier, prior research suggests that a positive association exists between OAs and civic engagement (Zarrett et al, 2021). Yet, this association might differ depending on the type of activity practiced in adolescence, as these are thought to offer different socialization experiences (Larson et al, 2006).…”
Section: Oas As Socialization Contexts Conducive To the Adoption Of Pebsmentioning
confidence: 85%
See 4 more Smart Citations
“…As mentioned earlier, prior research suggests that a positive association exists between OAs and civic engagement (Zarrett et al, 2021). Yet, this association might differ depending on the type of activity practiced in adolescence, as these are thought to offer different socialization experiences (Larson et al, 2006).…”
Section: Oas As Socialization Contexts Conducive To the Adoption Of Pebsmentioning
confidence: 85%
“…These models, as well as empirical studies, strongly suggest that PEAs could later translate into PEBs (Yuriev et al, 2020). We thus believe that some types of OAs considered in this study could possibly foster PEAs, since they all have been shown to foster civic engagement to different extents (Zarrett et al, 2021). In turn, PEAs should be positively associated with PEBs.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations